Rhamnolipids: solution against Aedes aegypti? - Silva, Vinicius L.; Lovaglio, Roberta B.; Von Zuben, Claudio J.; Contiero, Jonas (Frontiers in Microbiology, 2015)
Aedes aegypti mosquitoes are the primary transmitters of dengue fever, urban yellow fever and chikungunya viruses. This mosquito has developed resistance to the insecticides currently used to control their populations. These chemical insecticides are harmful to the environment and can have negative effects on human health. Rhamnolipids are environmentally compatible biological surfactants, but their insecticidal activity has not been extensively studied. The present study evaluated the potential larvicidal, insecticidal and repellent activities of rhamnolipids against Aedes aegypti. At concentrations of 800, 900 and 1000 mg/L, rhamnolipids eliminated all mosquito larvae in 18 hours and killed 100% of adults at 1000 mg/L. According to the results it may be conclude that rhamnolipids should be applied to control larvae and mosquitos besides present the repellency activity against Aedes aegypti.